Why Are Health Disparities Everyone's Problem? - Cooper, Lisa (Johns Hopkins University Press, 2021)
How can we all work together to eliminate the avoidable injustices that plague our health care system and society?Health is determined by far more than a person's choices and behaviors. Social and political conditions, economic forces, physical environments, institutional policies, health care system features, social relationships, risk behaviors, and genetic predispositions all contribute to physical and mental well-being. In America and around the world, many of these factors are derived from a lingering history of unequal opportunities and unjust treatment for people of color and other vulnerable communities. But they aren't the only ones who suffer because of these disparities-everyone is impacted by the factors that degrade health for the least advantaged among us.In Why Are Health Disparities Everyone's Problem? Dr. Lisa Cooper shows how we can work together to eliminate the injustices that plague our health care system and society. The book follows Cooper's journey from her childhood in Liberia, West Africa, to her thirty-year career working first as a clinician and then as a health equity researcher at Johns Hopkins University. Drawing on her experiences, it explores how differences in communication and the quality of relationships affect health outcomes. Through her work as the founder and director of the Johns Hopkins Center for Health Equity, it details the actions and policies needed to reduce and eliminate the conditions that are harming us all. Cooper reveals with compelling detail how health disparities are crippling our health care system and society, driving up health care costs, leading to adverse health outcomes and ultimately an enormous burden of human suffering. Why Are Health Disparities Everyone's Problem? demonstrates the ways in which everyone's health is interconnected, both within communities and across the globe. Cooper calls for a new kind of herd immunity, when a sufficiently high proportion of people, across race and social class, become immune to harmful social conditions through "vaccination" with solidarity among groups and opportunities created by institutional and societal practices and policies. By acknowledging and acting upon that interconnectedness, she believes everyone can help to create a healthier world.Features• Raises readers' health care inequities literacy through an approachable narrative with specific examples• Introduces the concept of "herd immunity" as it applies to building communal awareness of systemic injustices• Features sections that underscore key takeaways• Includes contributions from the world's leading minds through their research findings and quotations• Guides readers on what can be done at an individual level as a patient, public health professional, and community member • Includes inspiring stories of effective health equity studies and practices around the world, from Ghana's ADHINCRA Project addressing hypertension control to Baltimore's BRIDGE Study for depression in African Americans and the Maryland and Pennsylvania-based RICH LIFE Project for hypertension, diabetes, and other medical conditionsJohns Hopkins WavelengthsIn classrooms, field stations, and laboratories in Baltimore and around the world, the Bloomberg Distinguished Professors of Johns Hopkins University are opening the boundaries of our understanding of many of the world's most complex challenges. The Johns Hopkins Wavelengths book series brings readers inside their stories, illustrating how their pioneering discoveries benefit people in their neighborhoods and across the globe in artificial intelligence, cancer research, food systems' environmental impacts, health equity, science diplomacy, and other critical arenas of study. Through these compelling narratives, their insights will spark conversations from dorm rooms to dining rooms to boardrooms.